2002
DOI: 10.1108/01437730210435965
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and organizational effectiveness in multinational enterprises in southeast Asia

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 45 publications
(48 reference statements)
1
8
0
1
Order By: Relevance
“…was supported. This study's results are in line with research conducted by Rodsutti and Swierczek (2002), Inuwa (2016), Khan (2012), and Destari et al (2018). Based on the theory of Job satisfaction two factors from Herzberg (Lindsay et al, 1967), in the form of motivation and hygiene, have been felt by non-lecturer staff improving the performance of the employees or the results of their work.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…was supported. This study's results are in line with research conducted by Rodsutti and Swierczek (2002), Inuwa (2016), Khan (2012), and Destari et al (2018). Based on the theory of Job satisfaction two factors from Herzberg (Lindsay et al, 1967), in the form of motivation and hygiene, have been felt by non-lecturer staff improving the performance of the employees or the results of their work.…”
Section: Resultssupporting
confidence: 92%
“…Contradictory findings might be due to different individual factors, which contributed to job satisfaction. However, previous researchers have reported that job satisfaction is an essential element and positively affects job performance (Rodsutti and Swierczek, 2002)…”
Section: Job Satisfaction and Employee Performancementioning
confidence: 96%
“…Various researchers have established conceptual and empirical studies that report the relationship between intrapreneurship and firm performance as regards small and medium-sized companies (Antoncic & Hisrich, 2001;Champathes Rodsutti & Swierczek, 2002;Wiklund & Shepherd, 2003). In the case of developed economies, intrapreneurship has a positive relationship with corporate performance (Hornsby et al, 2002;Lumpkin & Dess, 2001).…”
Section: Intrapreneurship and Firm Performancementioning
confidence: 99%
“…Various individual elements which affect job satisfaction might explain the conflicting results. While previous research has shown that job happiness is an essential factor that impacts work performance, human resource professionals are still attempting to figure out what function job satisfaction plays in the success of multicultural workforces ( Champathes Rodsutti and Swierczek, 2002 ). Nolan (2012) stated that globalization has significantly altered the aspects of work for employees, posing a tough opportunity for management staff seeking to improve employee job satisfaction.…”
Section: Introductionmentioning
confidence: 99%